2021
DOI: 10.1016/j.artmed.2021.102098
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing evidence-based medicine with natural language argumentative analysis of clinical trials

Abstract: In the latest years, the healthcare domain has seen an increasing interest in the definition of intelligent systems to support clinicians in their everyday tasks and activities. Among others, also the field of Evidence-Based Medicine is impacted by this twist, with the aim to combine the reasoning frameworks proposed thus far in the field with mining algorithms to extract structured information from clinical trials, clinical guidelines, and Electronic Health Records. In this paper, we go beyond the state of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Understanding how a stressor impacts the cell cycle is just one of the many outcomes that a decision maker would consider when establishing public policy around potential carcinogens but cellular level outcomes are just one of the many streams of evidence that includes amongst other endpoints genetic markers, and evidence on humans and animals is weighted treated differently when determining if there is a sufficient amount of evidence to change policy. We also do not attempt to differentiate between major and minor claims, however human inter-rater reliability to establish this distinction has been reported as low [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding how a stressor impacts the cell cycle is just one of the many outcomes that a decision maker would consider when establishing public policy around potential carcinogens but cellular level outcomes are just one of the many streams of evidence that includes amongst other endpoints genetic markers, and evidence on humans and animals is weighted treated differently when determining if there is a sufficient amount of evidence to change policy. We also do not attempt to differentiate between major and minor claims, however human inter-rater reliability to establish this distinction has been reported as low [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The post error analysis found that the text needed to address a query appeared at the end of the abstract, which suggests that sentences were likely from the result and conclusion sections. In contrast to argumentation systems that strive to identify major claims [ 25 ] or to differentiate between major and minor claims, which has been shown to have low inter-rater reliability [ 26 ] we make no judgments regarding the veracity of a claim. Instead, directionality and negation of each claim are show to the decision maker as six discrete steps from refuting to negated refute, neutral, negated neutral, negated support, and finally to supporting evidence.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[9]), identifying the claims, their reasons and relationships between claims from clinical trials to inform medical decision making (e.g. [34]), or detecting fallacies from the transcripts of the United States Presidential Debates [39]. Online debates, such as those on Reddit or Twitter for example, can be converted into the argumentation framework by first defining nodes or arguments corresponding to each well-defined logical claim, and drawing signed edges representing supports or attacks between them.…”
Section: Background and Related Workmentioning
confidence: 99%
“…First, it exploits novel state-of-the-art neural models for the analysis of clinical trials, going beyond the link prediction task by labelling argument relations (i.e., to label as attack or support the relations holding between the identified argument components). Second, it goes beyond PICO element identification by allowing for the automatic analysis of the effect of an intervention on the observed outcome parameters [Mayer et al, 2021]. Finally, a refactoring of the ACTA architecture allows now for a modular solution, such that, through a REST API, the different ACTA 2.0 modules are made available to be integrated by external systems.…”
Section: Introductionmentioning
confidence: 99%